Mercury Accumulation in Commercial Varieties of Oryza sativa L. Cultivated in Soils of La Mojana Region, Colombia - Germán Enamorado-Montes (MDPI AG, 2021)
The Hg accumulation in different commercial varieties of Oryzasativa L. was evaluated in the region of La Mojana, Colombia, where rice cultivation has become the staple food of the population living in this area. The varieties studied were Fedearroz-473 (FA473), Fedearroz-2000 (FA2000), and Fedearroz-Mocari (FAM). Soil spiked at different Hg levels was evaluated, (130, 800, and 1500 µg kg−1) using a 32 factorial design that consisted of 3 (rice varieties) × 3 (Hg contents). The biomass, 1000-grain weight, and the accumulation of Hg in the roots, grains, and husks were determined. The highest biomass was found in the FA473 (308.76 ± 108.26 g), and the lowest was found in FAM (144.04 ± 26.45 g) in the 1500 µg kg−1 Hg soil in both cases. The weight per 1000-grains decreased significantly in the soil containing 800 µg of Hg kg−1. Hg accumulation in the organs of the evaluated varieties was higher in the roots, followed by in the husks and grains. The Hg in the rice grains of the evaluated varieties presented levels close to the permissible limit of the Chinese standard (20 μg Hg kg−1) in the evaluated soils and were only exceeded by FA473. Although in natural soil concentrations, the non-cancer health risk (HQ) from rice consumption was lower for FA473 and FAM; Hg enrichment in the soil of La Mojana region may endanger the health of future populations due to their high consumption of rice.